Investment management : notes and cases - Gopez, Eduardo C. (Quezon City, Philippines : U.P Business Research Foundation, Inc., 1972)
Primarily intended for university students, this book is also designed to meet the needs of businessmen, the personnel of business and financial institutions, and the general reader.
Part I. Introduction -- Part II. Cases
Includes index.
Keywords: MANAGEMENT